Pengaruh Literasi Keuangan, Pemahaman Shariah Governance Terhadap Keputusan Penggunaan Jasa Perbankan Syariah - Yurmaini; Muhammad Riduan Harahap; Erliyanti; Tetti Maisyaroh (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The aim of this study was to analyze the existence of Islamic financial literacy and Shariah Governance on student decisions in using Islamic banking services. The object of this research is students of the Sharia Economics Study Program, Islamic Faculty of Al-Washliyah University, Medan.The method used is multiple linear regression analysis with data processing using SPSS version 25. Independent variables in this study are the Level of Islamic Financial Literacy and Understanding of Sharia Governance, while the dependent variable in the study is Student Decisions in Using Islamic Banking Services. The results showed that the independent variables (level of Islamic financial literacy and understanding of sharia governance) simultaneously had a significant effect on student decisions, which was 0.000 less than 0.05. And in the R Square regressi on test, the variables X1 and X2 can simultaneously influence the Y variable by only 66.8%, the remaining 33.2% is influenced by other factors outside the study. Then, partially Islamic financial literacy and sharia governance also have a significant effect on student decisions in using Islamic banking services.